Long - term concequences of subdural hematoma on quality of life - Wojciech Czyżewski; Jakub Litak; Bartłomiej Kulesza; Agnieszka Rolińska; Dominik Staniewicz; Cezary Grochowski; Rafał Kruk; Bartłomiej Tyzo (Kazimierz Wielki University, 2018)
Subdural hematoma (SDH) could be an acute state required rapid neurosurgical decompression , could also represent chronic form ; both develope after head trauma as well. Long term influence on a quality of life depend on many factors. Reaserchers put a lot of effort to find those wchich play most predictive role.